Pelatihan Simulasi Akad Nikah Masa Pandemic Covid-19 Pada Lingkungan Keluarga Mahasiswa STAIN Mandailing Natal - Suryadi Nasution; Raja Ritonga; Akhyar Akhyar; Muhammad Ikbal (Janaka, Jurnal Pengabdian Masyarakat, 2021)
Wedding simulations involving family, neighbors and friends were reactive activities in Islamic Law learning innovations that were carried out online as a result of Covid-19 which was hitting the world. Islamic law online learning which has been limited theoretically to students in the campus environment, now can be executed more practically by involving stakeholders such as family, neighbors and friends. The simulation method was given in three stages; mentoring, training and accompaniment. The simulation process was carried out online with video conference through the Zoom application. Through this simulation, it was seen that the students were actively involved in taking on the role as simulation organizer as well as being active as training participants. Along with this, parents, friends, neighbors, and the society who took part of this had high enthusiasm in following the wedding simulation which was organized by the dedicated Team with very positive satisfaction rates